Foliar application of plant growth regulators to 'Crimson Seedless' grapevine influences leaf age - Amaro, Amanda Cristina Esteves [UNESP]; Souza, Essione Ribeiro [UNESP]; Santos, Laíse Sousa; Baron, Daniel; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Southern Cross Publishing, 2020)
We hypothesized that phytohormones and essential mineral nutrients influence the duration of leaf photosynthetic activity, fruit production and quality. We used a randomized block design, with four treatments and six replicates. Two commercial products were studied: Stimulate® (Stim), which is composed of a mixture of 0.009% cytokinin [N6-furfuryladenine or kinetin (Kt)], 0.005% auxin [4-indole-3-butyric acid (IBA)], and 0.005% gibberellin [gibberellic acid (GA3)], and Hold® (CoMo), which is composed of 2% cobalt and 3% molybdenum. These products were applied alone or in combination at different concentrations as follows: T1-control, T2-1.8 L ha-1 Stim, T3-1.8 L ha-1 Stim + 1.0 L ha-1 CoMo, and T4-1.8 L h-1 Stim + 1.5 L ha-1 CoMo. The treatments were applied via foliar spraying at three phases: the inflorescence primordial stage (19 days after pruning [DAP]), the point at which the berries were 6 to 8 mm in diameter (49 DAP), and the initiation of berry elongation (56 DAP). We revealed that in semiarid conditions, the grapevines were characterized by evergreen leaves (do not lose their leaves) that maintained their photosynthetic capacity throughout their lifecycles (133 days after sprouting). The application of Stim alone (T2) yielded the maximal net CO2 assimilation rates and increased the carboxylation efficiencies, which indicated that this treatment might improve the photosynthetic output. These effects led to increases in the average mass, total length and width of the clusters per plant and decreased acidity level. Thus, we recommend the application of T2 for grapevines.
Keywords: Auxin; Cobalt; Cytokinin; Gibberellin; Molybdenum; Vitis vinifera L